The Vereeniging riots of 1937 (Historia, 2021)
On a Sunday afternoon in the spring of 1937, in the black township adjacent to Vereeniging in the southern Transvaal, two policemen were killed and one seriously injured by an angry black crowd. As those policemen were white, a wave of indignation swept through the white community culminating in a boisterous meeting during which revenge on blacks was demanded. Feelings ran so high that an unsuspecting black passerby was indiscriminately set upon and brutally assaulted by the white crowd. The Government responded by appointing a commission of enquiry into the incident in the black township; the South African Institute of Race Relations, a liberal white organisation, sent its own commission to Vereeniging; court cases followed and pressmen flocked to the area to gather information for their newspapers. The events were even mentioned in the overseas media.
Keywords: Political unrest; Black resistance; History; Vereeniging riots; Race relations; Political history; Historia; South African Political History; Politics; 1937